Da nova direita ao bolsonarismo: usos da ditadura militar brasileira pelo canal do Youtube Folha Política - Barbosa, João Marcos Santiago Monteiro (2022)
The present dissertation is the product of a research on the uses of the Brazilian military dictatorship by the channel, from the Youtube platform, entitled Folha Política. Our central question can be summarized as follows: how was the historical experience of the military dictatorship in Brazil (1964-1985) reconstructed in the videos produced by Canal Folha Política during the years 2016 to 2020? To provide an answer to this question, we consider it important, first of all, to reconstruct the trajectory of this channel: who created it? In what context? With what goals? What changes took place in the channel during the period 2016 and 2020? We could see, in our research, that the creation of the channel, in 2016, was directly related to the mobilizations of the so-called New Right in favor of the impeachment of President Dilma Roussef and that, in 2018, during the campaign for the presidential elections, the Folha Política verticalized its political position, fully adhering to Bolsonarism. In this way, our research was able to focus on the uses of the Brazilian military dictatorship in a contextualized way, understanding the relationships between the interpretations of the past and the interests of the present. We note that the channel mobilizes a predominantly exemplary and monumental Historical Consciousness. Through nostalgia and monumentalization, he builds the idea that the dictatorship era was qualitatively better than the present. This mobilization of the past, aiming to restore lost values, or keep them in the face of the possibility of loss, also occurs with the objective of keeping its subscribers engaged in favor of current banners. For this to happen, the channel maintains its followers with a feeling of suspicion and hatred against the left-wing segments, they make monumental celebrations about the Brazilian military dictatorship, alluding to events that give a feeling of victory against a common enemy. In addition, Folha Política also uses euphemisms to appease the controversial speeches of people close to President Bolsonaro that involve the past of the dictatorship in Brazil.